Resilience in restaurants in Latin America. A systematic review (2020-2024) - Salas Carrera, Martín (2025)
During and as a consequence of the pandemic, the world experienced significant structural changes. Various productive sectors had to restructure many of their processes to survive. Among these, the gastronomic industry was severely affected by multiple restrictions, changes in its internal production and business dynamics, and safety regulations, among other factors. Many of these businesses went bankrupt, while others managed to reinvent themselves, building resilience to adapt to new, previously unknown circumstances. This review aimed to analyse studies on the strength of restaurant businesses in Latin America. The PRISMA method was employed, using the following databases: Scopus, WOS, Dialnet, SciELO, ProQuest, EBSCO, Redalyc, Emerald, ERIC and Google Scholar. Among the inclusion criteria, (i) publications were considered to be in Spanish, Portuguese, or English, and (ii) the studies were conducted in Latin America, and published between the years 2020 and 2024. The overall conclusion was that resilience was fundamental as a basis for adapting and restructuring business models, in which flexibility, innovation and creativity helped in reinventing themselves to continue operating.